The The Influence of Forest Control Policies and Multi-Actor Coordination on the Level of Forest and Land Fires in South Sumatera Province - Alisyahbana, M. Iqbal; Alfitri, Alfitri; Lionardo, Andries; Thamrin, M. Husni (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study aims to examine the relationship between forest and land fire control policies, multi-actor coordination, and the level of forest and land fires in South Sumatra Province. Using a quantitative approach with Structural Equation Modeling-Partial Least Squares (SEM-PLS), the study analyzes how these variables interact and influence each other. The findings reveal that multi-actor coordination plays a more significant role in reducing forest and land fires than the forest and land fire control policies themselves. The policy's impact on fire reduction, while positive, is limited compared to the effects of effective coordination among various actors such as the government, private sector, and local communities. Additionally, coordination acts as a mediator, enhancing the effectiveness of fire control policies. The results emphasize the importance of strengthening multi-actor coordination, improving the implementation of fire control policies, and fostering greater community involvement in fire prevention efforts. The study concludes that although policies are important, the collaboration between all stakeholders is crucial for achieving better outcomes in fire management.